2007
DOI: 10.1105/tpc.107.051516
|View full text |Cite
|
Sign up to set email alerts
|

Light-Independent Phytochrome Signaling Mediated by Dominant GAF Domain Tyrosine Mutants ofArabidopsisPhytochromes in Transgenic Plants

Abstract: The photoreversibility of plant phytochromes enables continuous surveillance of the ambient light environment. Through expression of profluorescent, photoinsensitive Tyr-to-His mutant alleles of Arabidopsis thaliana phytochrome B (PHYBY276H) and Arabidopsis phytochrome A (PHYAY242H) in transgenic Arabidopsis plants, we demonstrate that photoconversion is not a prerequisite for phytochrome signaling. PHYBY276H-expressing plants exhibit chromophore-dependent constitutive photomorphogenesis, light-independent phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
218
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 138 publications
(236 citation statements)
references
References 92 publications
14
218
2
2
Order By: Relevance
“…Previous screens have used a COLD, CIRCADIAN RHYTHM AND RNA BINDING2 (CCR2)::LUCIFERASE (LUC) reporter (Columbia accession [Col]) to measure circadian rhythms in the dark (Martin-Tryon et al, 2007), and so we generated Col plants containing both the YHB allele and the CCR2::LUC reporter in addition to introducing a CCA1:: LUC2 reporter into existing YHB (Landsberg erecta [Ler]) lines (Hu et al, 2009). Introduction of the YHB allele confers shortened hypocotyls and expanded cotyledons in Ler seedlings grown in darkness or in constant light (Su and Lagarias, 2007;Hu et al, 2009). Similar short hypocotyls were observed in our newly generated YHB (Col) lines when compared with wildtype Col controls grown under white light (P , 0.05; Fig.…”
Section: Yhb Sustains Core Clock Transcript Cycling In Light-grown Plsupporting
confidence: 58%
See 4 more Smart Citations
“…Previous screens have used a COLD, CIRCADIAN RHYTHM AND RNA BINDING2 (CCR2)::LUCIFERASE (LUC) reporter (Columbia accession [Col]) to measure circadian rhythms in the dark (Martin-Tryon et al, 2007), and so we generated Col plants containing both the YHB allele and the CCR2::LUC reporter in addition to introducing a CCA1:: LUC2 reporter into existing YHB (Landsberg erecta [Ler]) lines (Hu et al, 2009). Introduction of the YHB allele confers shortened hypocotyls and expanded cotyledons in Ler seedlings grown in darkness or in constant light (Su and Lagarias, 2007;Hu et al, 2009). Similar short hypocotyls were observed in our newly generated YHB (Col) lines when compared with wildtype Col controls grown under white light (P , 0.05; Fig.…”
Section: Yhb Sustains Core Clock Transcript Cycling In Light-grown Plsupporting
confidence: 58%
“…Previous work has demonstrated that YHB is sufficient to induce photomorphogenesis and to initiate transcriptional cascades that mimic red light-induced phy signaling in the absence of light (Su and Lagarias, 2007;Hu et al, 2009). The circadian system is exquisitely sensitive to changes in day length and light intensity (Salomé et al, 2008;Jones, 2009), so we were curious whether the YHB allele would mimic phyB-mediated light input into the circadian system.…”
Section: Yhb Sustains Core Clock Transcript Cycling In Light-grown Plmentioning
confidence: 99%
See 3 more Smart Citations